2000
DOI: 10.1590/s0100-83582000000100006
|View full text |Cite
|
Sign up to set email alerts
|

Influência de chuva simulada após aplicação de herbicidas em pós-emergência, sobre o controle de plantas daninhas, em solo com dois níveis de umidade

Abstract: RESUMO1 Recebido para publicação em 25/03/98 e na forma revisada em 27/09/99.Trabalho financiado pelo CNPq. 2 Engº Agrº, Pós-graduando no DFT/UFV, Secretaria da Pós-graduação, DFT/UFV, Viçosa/MG, cep: 36571-000. 3 Engº Agrº, Professor Adjunto no DFT/UFV, Viçosa/MG, CEP: 36571-000. Dois experimentos foram conduzidos em 1995, em casa-de-vegetação do Departamento de Fitotecnia da Universidade Federal Viçosa, Viçosa-MG, com o objetivo de avaliar a influência da chuva após a aplicação de herbicidas, no controle de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(4 reference statements)
1
2
0
2
Order By: Relevance
“…The absorption of glyphosate potassium salt formulation is slow and if there is rainfall, it may be washed and this reduces the control of % of these species. The obtained results by several researchers have shown that the absorbtion time of glyphosate in the potassium salt formulation ranges from 4 to 8 h (Bastiani et al, 2000;Jakelaitis et al, 2001;Martini et al, 2003;Werlang et al, 2003;Martins et al, 2009). During evaluation of the size of the stomata, a correlation was verified with the microscopic analysis discussed before (Figure 2) and it was observed that with the passage of time, there was a reduction in the width while the length did not experience any substantial change.…”
Section: Anatomical Studiessupporting
confidence: 55%
“…The absorption of glyphosate potassium salt formulation is slow and if there is rainfall, it may be washed and this reduces the control of % of these species. The obtained results by several researchers have shown that the absorbtion time of glyphosate in the potassium salt formulation ranges from 4 to 8 h (Bastiani et al, 2000;Jakelaitis et al, 2001;Martini et al, 2003;Werlang et al, 2003;Martins et al, 2009). During evaluation of the size of the stomata, a correlation was verified with the microscopic analysis discussed before (Figure 2) and it was observed that with the passage of time, there was a reduction in the width while the length did not experience any substantial change.…”
Section: Anatomical Studiessupporting
confidence: 55%
“…Em outro estudo da influência da chuva simulada sobre diferentes formulações de nicosulfuron, constatou-se maior eficácia do herbicida, para o controle de Brachiaria plantaginea, quando os intervalos sem chuva foram aumentados de 30 minutos após a aplicação, para plantas mantidas em solo com elevada umidade. Em solo com menor umidade, a eficácia foi muito menor, mesmo quando a chuva ocorreu 120 minutos após a aplicação (BASTIANI et al, 2000). BOVEY et at.…”
Section: Introductionunclassified
“…Moreover, the current evaluation analyzed only the machinery calibration, without any connection with the efficiency of the control, neither evaluated the time of application, which are the most important factors for the operational effectiveness. Bastiani et al (2000) showed in an experiment that control efficiency in advanced plants was not achieved by comparing the application of an herbicide in early stage and late stage weeds. Therefore, the planning of the activities must be up to date, in order not to compromise the quality of the operation besides the proper functioning of the equipment.…”
Section: Herbicidementioning
confidence: 99%